A biographical nadir: life stories of adults who were educated in childhood at therapeutic boarding schools for 'children at risk'. Issue 4 (21st April 2023) - Frantsman-Spector, Alin; Shoshana, Avihu
Abstract: This article examines the life stories of adults in Israel who were defined as 'at-risk children' in their childhood and removed from their homes by court order to therapeutic boarding schools against the backdrop of 'inadequate parenting, ' 'neglect, ' and/or 'abuse.' The findings reveal how graduates experienced their forced removal from the family home as a life event that shattered their phenomenological taken-for-granted knowledge. Graduates also reported a unique life story form of a biographical nadir ('You can't live lower than that'). This life story form also involves a constant reflexive engagement with 'biographical noise' expressed by the fear of 'going backwards' and the ongoing need to understand the parents' decision in light of their living conditions. The article highlights the unique characteristics of the graduates' life story form, the subjective experience of multiple types of self-affiliated with different times, and the long-term ramifications of using the concept of risk.